Constructing the intellectually disabled person as a subject of education: a discourse analysis using Q-methodology - McKenzie, Judith Anne (Rhodes University, Faculty of Humanities, Department of Psychology, 2009)
The education of intellectually disabled (ID) people is constructed within mass education systems as a problem requiring specialised intervention, separation from "normal" school contexts and the application of professional expertise. A social model of disability resists these practices from a human rights perspective and underpins an inclusive education approach. In this study, a post-structuralist disability studies theoretical framework, drawing particularly on the work of Foucault, was used to examine discourses that construct the intellectually disabled person as a subject of education. The study was conducted in Buffalo City, South Africa at a time when an inclusive education policy is being implemented in the country. The research questions were: What discourses are deployed in the representation and educational practices of those identified as ID? What are the effects of these discourses in constructing the ID subject and associated educational practice? The study utilises Q-methodology, a factor analytic method that yields whole patterns of responses for analysis. A process of sorting selected statements along the dimension of agree to disagree was completed by three groups of participants, namely adults with ID, parents of people with ID and professionals working with ID. Discourses of representation and of educational practice were identified through statistical and interpretive analysis, following the discourse analysis school of Q-methodology. The findings of this study reveal the operation of power in a medico-psychological gaze that makes ID visible and supervises disability expertise within education. Representations of ID suffused with religious notions support the exercise of pastoral power by disability experts. Human rights discourses in education can marginalise ID people if applied uncritically. Fixed notions of impairment constrain an intellectually disabled subject who is vulnerable and incompetent. This study argues instead for a theory of (poss)ability, underpinned by an understanding of the situational and shared nature of competence and a fluid conception of impairment. Human rights should be supplemented by an ethics of care and belonging in the community (ubuntu). A research agenda supporting this effort would examine the ways in which ID people work on themselves as subjects (subjectivisation) and explore the potential for resistance in this process.
Keywords: Foucault, Michel, 1926-1984; Learning disabled -- Education -- South Africa; Discourse analysis -- Methodology; Discourse analysis; Children with mental disabilities -- Education -- South Africa; Q technique; Special education -- South Africa; Children with disabilities -- Education -- South Africa; Right to education; Intelligence tests -- South Africa